A new selenosteid placoderm from the Late Devonian of the eastern Anti-Atlas (Morocco) with preserved body outline and its ecomorphology - Jobbins, Melina; Rücklin, Martin; Ferrón, Humberto G.; Klug, Christian (Frontiers in Ecology and Evolution, 2022)
Placoderms are an extinct group of early jawed vertebrates that play a key role in understanding the evolution of the gnathostome body plan, including the origin of novelties like jaws, teeth and pelvic fins. As placoderms have a poorly ossified axial skeleton, preservation of the mainly cartilaginous axial and fin elements is extremely rare, contrary to the heavily mineralized bones of the skull and thoracic armor. Therefore, the gross anatomy of the animals and body shape are only known from a few taxa and reconstructions of the swimming function and ecology are speculative. Here, we describe articulated specimens preserving skull roofs, shoulder girdles, most fins, and body outlines of a new derived arthrodire. Specimens of the selenosteid Amazichthys trinajsticae gen. et sp. nov. display a skull roof with reticular ornamentation and raised sensory lines like Driscollaspis, a median dorsal plate with a unique sharp posterior depression, the pelvic girdle, the proportions and shape of the pectoral, dorsal and caudal fins as well as a laterally enlarged region resembling the lateral keel of a few modern sharks and bony fishes. Our new phylogenetic analyses support the monophyly of the selenosteid family and places the new genus in a clade with Melanosteus, Enseosteus, Walterosteus and Draconichthys. The shape of its body and heterocercal caudal fin in combination with the pronounced ‘lateral keel’ suggest Amazichthys trinajsticae was an active macropelagic swimmer capable of reaching high swimming speeds.